Energy-Dispersive Total-Reflection Resonant Inelastic X-ray Scattering as a Tool for Elemental Speciation in Contaminated Water - Robledo, José Ignacio (2018)
This work presents a state-of the-art analytical methodology, by which chemical state information on metallic elements is obtained for liquid samples in a fast and simple manner. This method overcomes limitations of conventional X-ray techniques, such as X-ray absorption spectroscopy, by applying resonant inelastic X-ray scattering under total reflection geometry (TRIXS). TRIXS is particularly applicable for the analysis of small quantity of liquid samples deposited on polished reflectors. This feature is relevant for the chemical speciation of metallic trace elements contained in water samples, since the degree of their toxicity depends crucially on the concentration of specific chemical species included. The analytical merits of the proposed methodology were studied at Elettra Sincrotrone Trieste and at the Brazilian Synchrotron Light Laboratory. Contaminated water samples with low concentration of different chromium and manganese compounds were measured. Results prove the analytical potential of the TRIXS technique in characterizing different chemical species of metallic elements in water samples.